The Moleculer Mechanism of Squalen on Cisplatin-induced Nefrotoxicity - Sakul, Ayse Arzu Sayin; Ozansoy, Mehmet; Ayla, Sule; Gunal, Mehmet Yalcin; Yozgat, Yasemin; Kazancioglu, Rumeysa; Kilic, Ulkan (Wiley-Blackwell, 2016)
[Abstract Not Available]